The Metformin Immunoregulatory Actions in Tumor Suppression and Normal Tissues Protection - Gupta, Jitendra; Jalil, Abduladheem T.; Abd Alzahraa, Zahraa Hamzaa; Aminov, Zafar; Alsaikhan, Fahad; Ramírez-Coronel, Andrés Alexis; Ramaiah, Pushpamala; Najafi, Masoud (Current Medicinal Chemistry, 2024)
The immune system is the key player in a wide range of responses in normal tissues and tumors to anticancer therapy. Inflammatory and fibrotic responses in normal tissues are the main limitations of chemotherapy, radiotherapy, and also some newer anticancer drugs such as immune checkpoint inhibitors (ICIs). Immune system responses within solid tumors including anti-tumor and tumor-promoting responses can suppress or help tumor growth. Thus, modulation of immune cells and their secretions such as cytokines, growth factors and epigenetic modulators, pro-apoptosis molecules, and some other molecules can be suggested to alleviate side effects in normal tissues and drug-resistance mechanisms in the tumor. Metformin as an anti-diabetes drug has shown intriguing properties such as anti-inflammation, anti-fibrosis, and anticancer effects. Some investigations have uncovered that metformin can ameliorate radiation/chemotherapy toxicity in normal cells and tissues through the modulation of several targets in cells and tissues. These effects of metformin may ameliorate severe inflammatory responses and fibrosis after exposure to ionizing radiation or following treatment with highly toxic chemotherapy drugs. Metformin can suppress the activity of immunosuppressive cells in the tumor through the phosphorylation of AMP-activated protein kinase (AMPK). In addition, metformin may stimulate antigen presentation and maturation of anticancer immune cells, which lead to the induction of anticancer immunity in the tumor. This review aims to explain the detailed mechanisms of normal tissue sparing and tumor suppression during cancer therapy using adjuvant metformin with an emphasis on immune system responses.
Keywords: cancer